SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN - Rista Yusma Yanti (UNISAN JURNAL, 2024)
Academic supervision is a series of activities to help the teachers indeveloping their ability to manage the learning process in order to achieve the learning targets. Supervision which was conducted by SMA IT Khazanah Kebajikan Palembang was an aid that guides the teacher in planning the learning, implementing the learning process, evaluating the students’ learning outcome, and following up the supervision’s results in order to improve the quality of learning in SMA Tunas Mekar Indonesia Kota Bandar Lampung Khazanah Jati Agung. This study applied descriptive qualitative approach. As for the validity test using triangulation techniques data and sources, while the data analysis using interactive analysis techniques. Based on the research findings, it could be concluded as follows: (1) the principal’s academic supervision programs were arranged at the beginning of the school year by identifying the problems, setting the goals, and deteFrmining the implementation time in advance. Those activities engaged the roles of vice principal of curriculum, vice principal of quality guarantor, and teachers that were done systematically, (2) the implementation strategy of the principal’s academic supervision included: indirect and direct supervision, classroom visit supervision, and observation of the teachers’ activity inside as well as outside the classroom, and the following-up implementation of academic supervision result in the form of personal and group coaching. (3) The implication of principal’s academic supervision were: the improvement in the teachers’ ability in designing learning sets, implementing the learning process, the students’ learning outcomes. Keywords: Academic Supervision, Principal, The Learning Quality